Algerian immigration to France during the French occupation period 1830-1962 AD - a reading of the causes and motives - - BENFATIMA, Samia; HAFDELLAH, Boubaker (Social Sciences Journal)
Since its occupation of Algeria in 1830, France has sought to make it dependent on it, It has adopted a settlement policy aimed at eliminating the Algerian people completely. The Algerian economy is thus transformed from a subsistence farming economy to a monetary economy aimed at serving the French own economy. Thus, many economic, social and psychological causes are met to lead a number of Algerians to a sense of alienation within their homeland ruled by France. The latter tried hard to put the Algerians in a narrow space, deprived of their rights. Many Algerians chose foreign countries as a destination for emigration. So; the act of emigration was a form of resistance against France, a resistance that expresses resentment and rejected an abhorrent occupier. Through this resistance, the Algerian emigrants demanded freedom and respect and may be opportunities that are no longer provided by their usurped homeland